1971
DOI: 10.1136/jcp.24.5.444
|View full text |Cite
|
Sign up to set email alerts
|

Search for Serratia

Abstract: During a four-month period an intensive effort was made to isolate and identify everySerratia marcescensstrain present in the clinical material received for bacteriological assessment in the laboratory. Ten strains were isolated from eight patients, the organism possibly being responsible for infection in five of these patients.Serratia marcescensis thus commoner than expected and it is difficult to explain the fact that there are so few references to it as a pathogen in the British literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…A similar low incidence was found at Glasgow Royal Infirmary (Black, 1970). Information from colleagues in various parts of the country and, informally, from the Medical Research Council's Committee on Hospital Infection indicated that this was generally true in the U.K. A similar low incidence was reported to us from hospitals as far apart as Canada (personal communications from Dr F. A. Holden, University Hospital, Saskatoon, Mrs C. A. Johnston, Royal Jubilee Hospital, Victoria, and Dr D. H. Starkey, Queen Mary Veterans Hospital, Montreal) and Hong Kong (Dr C .…”
Section: Serratia Marcescens Isolatessupporting
confidence: 76%
“…A similar low incidence was found at Glasgow Royal Infirmary (Black, 1970). Information from colleagues in various parts of the country and, informally, from the Medical Research Council's Committee on Hospital Infection indicated that this was generally true in the U.K. A similar low incidence was reported to us from hospitals as far apart as Canada (personal communications from Dr F. A. Holden, University Hospital, Saskatoon, Mrs C. A. Johnston, Royal Jubilee Hospital, Victoria, and Dr D. H. Starkey, Queen Mary Veterans Hospital, Montreal) and Hong Kong (Dr C .…”
Section: Serratia Marcescens Isolatessupporting
confidence: 76%
“…Fifty-eight strains of S. marcescens and 2 strains of S. liquefaciens were isolated from 59 patients over a period of 14 months. The isolation rate was low compared with hospitals in the U.S.A. but was approximately twice that reported by Black & Hodgson (1971), who conducted a similar survey in Scotland, whether isolations per month or per specimen were compared. This difference may be fortuitous, but the possibility that there has been a recent, true increase in the occurrence of Serratia in British hospitals cannot be excluded.…”
Section: Discussionmentioning
confidence: 55%
“…1977. During a 4-month period Black & Hodgson (1971) isolated 10 strains of S. marcescens from clinical specimens examined in a routine bacteriology laboratory, Ball, McGhie & Geddes (1977) have reported 14 cases of infection with S. marcescens over an 8-month period and Tabaqchali, Chambers & Brooks (1977) in a preliminary report demonstrated a higher incidence. In contrast, Hedges, Rodrigues-Lemoine & Datta (1975) recorded only one or two Serratia isolations per annum in a laboratory handling about 60000 clinical specimens each year.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few reports of outbreaks of infection in the UK (Black & Hodgson, 1971;Rogers & Gittens, 1974;Ball, McGhie & Geddes, 1977;Meers et al 1978). …”
Section: Discussionmentioning
confidence: 99%